REFRESHING KADER KESEHATAN TENTANG BABY GYM BERBASIS KEARIFAN LOKAL - Marliana, Yunita; Najahah, Imtihanatun; IGA Putu Sri Wahyuni (Poltekkes Kemenkes Mataram, 2025)
Stunting in toddlers is a nutritional problem not only in Indonesia but also globally. The WHO states that stunting becomes a health problem when the prevalence reaches >20%. The stunting prevalence trend in Indonesia has changed significantly since 2014, reaching 37% and dropping to 21.6% in 2022. Based on data from the Indonesian Nutrition Status Survey (SSGI) from 2021 to 2022, the incidence of stunting increased from 24.4% to 21.6%, wasting from 7.1% to 7.7%, and underweight from 17.0% to 12.1%. West Nusa Tenggara Province has a stunting incidence of 31.4%, ranking it fourth in Indonesia. Community service activities aim to empower integrated health post (Posyandu) cadres by providing education and reinforcement about local wisdom-based baby gym. Results of community service activities: Most Posyandu cadres (17 people) had good knowledge, and 30 people (100%) were able to perform baby gym. Evaluation results showed that the cadres were able to teach baby gym to 30 mothers with babies and toddlers. It is hoped that mothers who have received education about baby gym can perform baby gym regularly with their babies and toddlers to support optimal child growth and development and prevent stunting.